2021
DOI: 10.3855/jidc.14345
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of COVID-19: Experience at a major tertiary care center in Pakistan

Abstract: Introduction: Limited data exist on clinical characteristics and outcomes of hospitalized COVID-19 patients in low-middle income countries. We aimed to describe the clinical spectrum and outcomes of hospitalized COVID-19 patients at a tertiary-care center in Karachi, Pakistan. Methodology: We conducted an observational study of adult COVID-19 patients hospitalized between February-June 2020. Patients with a discharge diagnosis of COVID-19 and PCR positivity were included. We created logistic regression m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 43 publications
3
25
0
1
Order By: Relevance
“…Over the same period studied, the Sindh Health Department COVID-19 report indicated that 76% of confirmed cases were below 50 years of age 26 with a similar trend was observed in national data. Nasir et al showed that there were no specific factors associated with hospital related morbidity and mortality of COVID-19 in Pakistan, except for an older age group 27 . These study samples were from between March and October 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Over the same period studied, the Sindh Health Department COVID-19 report indicated that 76% of confirmed cases were below 50 years of age 26 with a similar trend was observed in national data. Nasir et al showed that there were no specific factors associated with hospital related morbidity and mortality of COVID-19 in Pakistan, except for an older age group 27 . These study samples were from between March and October 2020.…”
Section: Discussionmentioning
confidence: 99%
“… 32 33 Similar to our finding, a significant association between lower SpO2 level or severe illness with older age and the presence of any comorbidity was reported in Pakistan. 22 Besides, the severe illness was significantly associated with radiological findings of pneumonia, 34 higher creatinine, 35 C reactive protein 18 and neutrophil:lymphocyte ratio. 36 37 A higher proportion of patients with low SpO 2 levels frequently received antibiotics, anticoagulants and glucocorticoid therapy.…”
Section: Discussionmentioning
confidence: 95%
“… 36 37 A higher proportion of patients with low SpO 2 levels frequently received antibiotics, anticoagulants and glucocorticoid therapy. 22 38 Other studies from Bangladesh also reported that antibiotics are the most commonly used medication during the treatment of COVID-19. 24 39 …”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations